Internet connectivity disruption in Namibia (Namibia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Namibia. Data sourced from IODA.
Network Disruption Incident ID: NA-2026-0008. Severity: critical. Confidence: 67%